Productivity, Profitability and Nutrient Uptake as Influenced by Tillage Practices and Irrigation Scheduling in Wheat (Triticum aestivum L.) under Subtropical Climatic Conditions - Kumar, Vineet; Naresh, R. K.; Kumar, Satendra; Tomar, S. S.; Khilari, Kamal; Singh, Raghuvir; Dwivedi, Ashish (International Journal of Bio-resource and Stress Management, 2016)
To evaluate the effect of different tillage practices and irrigation scheduling in wheat on a sandy loam, a field experiment was conducted at Crop Research Centre of Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut (U.P.) during Rabi season of 2013–14 and 2014–15. Five tillage crop establishment methods, viz. T1–wide raised beds, T2–narrow raised beds, T3–conventionaltillage, T4–reduced tillage, T5–zero tillage were kept in main plots and three irrigation scheduling practices, viz. I1–IW/CPE 0.45, I2-IW/CPE 0.60, I3-IW/CPE 0.75 were allotted to sub-plots in a split-plot design and replicated thrice. The result showed that number of grain spike-1, test weight, spike length and number of spikelet’s spike-1 were significantly higher with wheat sown on wide raised beds than all other tillage practices except narrow raised beds and zero tillage plots. Similarly furrow irrigated raised beds increased the mean grain yield of wheat significantly over rest of the plots and grain yield increased by and 18.3% over I1 and 8.6% over I2 in I3 irrigation schedule. Higher nutrient uptake (NPK) by grain and straw as well as total uptake were recorded under wide raised beds followed by zero tillage and narrow raised beds. The maximum gross income, net income, benefit: cost ratio was significantly higher in wide raised beds plots. Similarly the highest mean net profit (` 63616.6 ha-1) with mean B:C ratio of 2.14 was recorded with the application of three irrigations at 22, 65 and 105 DAS in wheat crop.